Sustainable Energy Solutions for Isolated Areas: A Case Study of PT Pertamina International Refinery RU IV Cilacap’s CSR Program: Solusi Energi Berkelanjutan untuk Daerah Terisolir: Studi Kasus Program CSR PT Pertamina International Refinery RU IV Cilacap - Shodikin, King Amil Hamzah Al Hakim; Nugroho, Aditya Anung Dwi; Rahmawati, Puji (Indonesian Journal of Innovation Studies, 2023)
This qualitative study examines the implementation of PT Pertamina International Refinery RU IV Cilacap’s Corporate Social Responsibility (CSR) program, focusing on sustainable energy solutions for isolated areas in Indonesia. The program, supporting the Energy Independent Village Movement, establishes a Hybrid Power Plant using solar and wind energy in Bondan Hamlet, an area lacking electricity access. The research analyzes the planning, execution, and evaluation of the CSR project, with a particular emphasis on stakeholder participation and community responses. The study concludes that the CSR program successfully aligns with the triple bottom line approach and adheres to ISO 26000 guidelines, contributing to sustainable energy development in isolated regions. Highlights: Uneven regional development in Indonesia has left some areas isolated and lacking basic needs, including energy. The Energy Independent Village Movement, supported by PT Pertamina International Refinery RU IV Cilacap’s CSR program, aims to address this issue by utilizing natural resources. Bondan Hamlet, an isolated area without electricity, was chosen as a pilot project for a Hybrid Power Plant program using solar and wind energy, which was successful in planning, implementing, and evaluating the project.